KEBIJAKAN UTANG DI SEKTOR PROPERTY, REAL ESTATE DAN BUILDING CONSTRUCTION - Kadiman, Febriana Fousta Dewi; Wibowo, Satriyo (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this research is to examine the impact of asset structure (SAT), liquidity (CR), profitability (ROA), dividend policy (DPR), institutional’s ownership (IO) and business risk (RISK) on debt policy. This research used property, real estate and building construction sector companies that listed in Indonesia Stock Exchange period 2015-2020 as the sample research. There are 42 data sampled from seven companies. Purposive sampling is used as the sample research method. Descriptive statistics and multiple regression analysis are used to analyze the data. The result of this research showed that ROA and RISK have positive and significant relationship with debt policy. While SAT, CR, DPR and IO have no influence to policy. Therefore, profitability and risk business should be concerned by the companies to make a decision about debt policy.